Browning and watercore disorders in 'Fuji' apples explored by means of X-ray computed tomography (CT) - Chigwaya, Kenias (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.